Jump height as performance indicator for the selection of youth football players to national teams - Augustsson, S. R.; Arvidsson, J.; Haglund, E. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Different jump tests such as the Countermovement Jump (CMJ), Abalakov Jump (AJ) and Standing Long Jump (SLJ) are often used in practice to evaluate muscular power and functional performance in football. These tests are also used in different selection processes and talent identification, but the significance of the tests for the selection of youth players to national teams are relatively unknown. The aim of this study was to compare jump ability between youth football players selected or not selected for the national team. METHODS: In this cross-sectional study, 22 players (aged 17±2 years), 11 national players (NP) and 11 non-national players (NNP) were evaluated in three different jump tests; CMJ, AJ and SLJ. Mean scores for the tests were analyzed and compared. RESULTS: Significant differences were found between the groups regarding jump height in favor of the NP group in both the CMJ (NP 39.9±5.0 cm vs. NNP 34.2±4.9 cm, P=0.013) and the AJ (NP 47.1±5.4 vs. NNP 40.9±4.7, P=0.010). No group difference was found regarding jump length in SLJ (NP 246.2±17.9 vs. NNP 232.9±16.5, P=0.084). CONCLUSIONS: The results suggest that tests, measuring jump height, could be used as a performance indicator and part of the selection process of youth football players to national teams, whereas the use of jump length could be questioned.